Cessation of e-cigarette use among adults in Malaysia : findings from a nationwide survey - Muhammad Fadhli Mohd Yusoff,; Ling, Jane Miaw Yn; Thamil Arasu Saminathan,; Jamaluddin Ab Rahman,; Wan Shakira Rodzlan Hasani,; Tania Gayle Robert Lourdes,; Lim, Kuang Hock; Sumarni Mohd Ghazali,; Mohamad Haniki Nik Mohamed, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The use of e-cigarettes has increased rapidly around the world including in Malaysia. However, a significant proportion of people who started using e-cigarettes later discontinued using them. The aim of this study is to identify prevalence of former e-cigarette use and factors associated with quitting, among Malaysian adults. This study is a part of a national household survey examining the use of e-cigarettes among Malaysian adults aged 18 years and above in 2016. A multistage stratified cluster sampling method was used in the survey. A bilingual (Malay and English) structured questionnaire was used and data was collected via face-to-face interview. Prevalence of current e-cigarette use and former e-cigarette use were determined. A multiple logistic regression model was used to identify factors associated with quitting e-cigarettes. A total of 4,288 adults participated in the survey, where 110 (3.2%) and 289 (8.6%) were identified as current and former e-cigarette users respectively. The following factors were significantly associated with quitting e-cigarette use: e-cigarette users who had no exposure to e-cigarettes at the workplace (aOR = 2.70; 95% CI: 1.39, 5.24); the perception that e-cigarette is more harmful to people compared to tobacco smoke (aOR = 2.46; 95% CI: 1.22, 4.97); and the perception that e-cigarettes do not help people to maintain cigarette abstinence (aOR = 2.19; 95% CI: 1.23, 3.92). This study contributes to a better understanding of the factors associated with cessation of e-cigarettes. Findings from this study can assist any e-cigarette cessation intervention measures such as strengthening on policy that prohibit e-cigarette use at workplace and increase advocacy on not using e-cigarette as a method to stop smoking.